The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.semarthrit.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of disease modifying agents for rheumatoid arthritis in the National Hospital and Ambulatory Medical Care Survey

Abstract: Objective We examined the treatment patterns among adults with rheumatoid arthritis (RA) and identified factors influencing access to traditional and biological disease modifying antirheumatic drugs (DMARDs). Methods We analyzed visits recorded in the National Ambulatory Medical Care Survey from 2005 to 2014 with a RA diagnosis. The primary outcome was DMARD use (traditional and/or biological). We included prescriptions of all RA-related treatments such as traditional and biological DMARDs, glucocorticoids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The unit of analysis is the ambulatory visit associated with an RA diagnosis and not persons with RA, and RA cases are not followed longitudinally over 12 years because different individuals are sampled every year. Similar to other studies using NAMCS data with acceptable accuracy, we used up to the first three diagnoses and eight medications to evaluate DMARD use for visits likely to have been for RA ( 13 , 14 ). However, diagnosis cannot be confirmed, and medication data are not validated against the prescription date, nor do they include dosage information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit of analysis is the ambulatory visit associated with an RA diagnosis and not persons with RA, and RA cases are not followed longitudinally over 12 years because different individuals are sampled every year. Similar to other studies using NAMCS data with acceptable accuracy, we used up to the first three diagnoses and eight medications to evaluate DMARD use for visits likely to have been for RA ( 13 , 14 ). However, diagnosis cannot be confirmed, and medication data are not validated against the prescription date, nor do they include dosage information.…”
Section: Discussionmentioning
confidence: 99%
“…In an early study using NAMCS data from 1996 to 2007, Solomon et al showed most visits coded with RA did not have an associated DMARD prescription ( 13 ). Another study using later NAMCS data showed any DMARD use was associated with visits with specialists and Medicare beneficiaries (2005‐2014) ( 14 ). However, these studies did not focus on older adults and did not evaluate variations in DMARD prescriptions by provider specialty over time.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors as data collection interval, race, provider type (general physician vs. specialist), and type of drug coverage are associated with the use of DMARDs or biological agents among RA patients [10], and financial burden of certain expensive biological agents, usually leads to insufficient treatment among RA patients [10]. The data collection interval in this study was between 1998 and 2012, and during which period, the most available biologics agents for RA were etanercept (etanercept was available in Taiwan was since May 12, 2005) and adalimumab (adalimumab was available in Taiwan was since Aug 19, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The use of biological agents has been associated with significantly increased rates of serious infections, including opportunistic infections and bacterial infections, in most studies [9], and the outcomes of adverse drug effects has resulted in most guidelines recommending biological agents to be used in patients who had responded poorly to or who were intolerant of one or more DMARDs [10]. According to one recent study [11], autoantibodies and markers of systemic or local inflammation can be present long before clinical arthritis, and the disease process evolves long before the disease is clinically detectable, i.e., early treatment in RA patients should be associated with improved outcomes [11].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms are often indicators of moderate stage RA or the sequential stages.The administration of long-term treatment medications is generally delivered to patients in moderate stage RA and beyond. These include a class of drugs called disease-modifying anti-rheumatic medications (DMARDs) such as methotrexate, hydroxychloroquine, and sulfasalazine, which aid in the suppression of inflammation [36].…”
Section: Introductionmentioning
confidence: 99%